KEY FOR THE GENERA OF CLERIDAE FROM CHILE (COLEOPTERA) (Acta Entomológica Chilena, 2022)
Eigtheen genera of Cleridae (Coleóptera) are recognized for the chilean fauna. The genera Eurymetomorphon,Chilioclerus, Eurymetopum and Silviella, synonymyzed by Kolivác (1997-1998), are maintainedas valid taxa. An illustrated key of identification of the genera is provided.
Keywords: Cleridae, Chile, genera, identification key